Factorial Invariance and Internal Structure of the Scale of the Students’ Role in the Cycle of School Violence (ERECVE) - Pérez-Morán, Juan C.; Rodríguez-Macías, Juan C. (Frontiers in Education, 2022)
The purpose of this study was to analyze evidence of construct validity of internal structure and factorial invariance for the Scale of the Students’ Role in the Cycle of School Violence (ERECVE, in Spanish). To that end, we relied on a database of 13,389 participants with a sample of Mexican low secondary education students: 6,935 female and 6,454 male. Participants had a mean age of 13.08 years (SD = 0.98). The dimensionality and fit of a reconfigured five-factor model were analyzed using Confirmatory Factor Analysis (CFA); nested models sequencing methods were applied subsequently to validate invariance between genders. The results from the dimensionality analysis support the reconfigured five-factor structure for the dimensions referring to the roles of victim, defender or conciliator, sole bully, social bully and bystander. Moreover, acceptable fit indices were obtained for the configurational, weak, strong and strict models after comparing the nested models. It was concluded that the reconfigured five-factor model is useful for measuring the roles of students in the cycle of school violence, and that the ERECVE achieves a simultaneous measurement invariance, thereby favoring the analysis of mean differences between genders.